Climate-Smart Strategies for Mitigating Abiotic Stresses in Cereal Crops: A Review: Climate-Smart Approaches for Cereal Stress Mitigation - Yashavanthakumar K J; Pravin Pawar; Basavaraj PS; Manoj Oak; Chandra Nath Mishra; Mamrutha HM; Suma Biradar; SA Desai; Navathe, Sudhir (Journal of Cereal Research, 2025)
Climate variability has intensified the frequency and severity of abiotic stresses, including drought, heat, salinity, waterlogging, nutrient deficiency or toxicity, chilling, ultraviolet radiation, and increased atmospheric CO2 levels. These stresses hamper plant growth by modifying physiological balance, biochemical processes, and gene expression networks, leading to significant reductions in yield and quality in major crops. Addressing these challenges requires a comprehensive understanding of plant adaptation, tolerance mechanisms, and strategies for mitigating stress. This review synthesises recent advancements in understanding the morpho-physiological, biochemical, and molecular responses of plants to various abiotic stresses and examines how this knowledge can inform climate-smart agricultural practices.  Conventional breeding, supported by high-throughput phenotyping and precision selection, is essential for crop improvement. Meanwhile, modern genomics and biotechnology—including marker-assisted selection, genomic selection, transcription factor engineering, and genome editing—facilitate targeted enhancement of stress resilience. Complementary innovations such as speed breeding, nanotechnology, microbiome engineering, and nutrient-efficient agronomy provide additional methods to enhance plant performance in challenging environments. The incorporation of artificial intelligence and machine learning into phenomics and genomic datasets has facilitated the modelling of complex genotype–environment interactions, expedited the identification of resilient genotypes, and enhanced the prediction of crop behaviour in future climates. The integration of genetic, agronomic, and digital methodologies in climate-smart agriculture offers a sustainable framework for mitigating the adverse effects of various abiotic stresses. The combined application of molecular breeding, resource-efficient management, and data-driven technologies is essential for achieving global food and nutritional security, sustaining ecosystem balance, and developing resilient agricultural systems in the context of unpredictable climate change.